The Art of Sculpture: Jan Patočka's Concept of Incarnate Being. Issue 50 (3rd July 2019) - Novák, Josef
ABSTRACT: Jan Patočka is known as a philosophical analyst of the phenomenological concept of the live-word ( Lebenswelt ), which contradicts the preoccupations expressed in Sir Herbert Read's Art of Sculpture . This essay interprets Patočka's "philosophy of sculpture" in the intellectual context of communist Czechoslovakia, arguing that he regarded sculpture as an incarnate being. His phenomenological interpretation defies all attempts to narrow such a being to the realm of mere haptic or visual sensibilities.